DYNAMIC TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN INDONESIA - Sofwatun Nida; Musyaffa Rafiqie; Saepudin Mashuri; Putri Nadha Setyaningrum; Arif Abdullah Sagran (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
Changes in the Islamic Religious Education curriculum are undeniable in Indonesia. The changes are in line with the development of the national curriculum in general. There are many articles about the development of the Islamic Religious Education curriculum in Indonesia, but all of them are protracted on the development of the national curriculum in general. This article aims to describe the characteristics of Islamic Religious Education in particular that have not been touched upon by previous articles. This literature research was carried out by reviewing articles and books on the development of the national curriculum and specifically about the Islamic Religious Education curriculum. Triangulation is carried out between one reference and another, classified according to sub-subjects, and finally conclusions are drawn. The results of the study show that there are five periods of changes in the Islamic Religious Education curriculum, namely the Pre-Independence Era when Islamic Religious Education materials were not found in schools, the ‘Orde Lama’ Era Islamic Religious Education lessons were optional at the request of the students' parents, the ‘Orde Baru’ Era Islamic Religious Education lessons gained a proportional position and portion, the Reform Era did not change but the forerunners of change were quite visible. In the New Indonesia era, the change in the Islamic Religious Education curriculum was very dynamic and this lesson became the spirit of all other subjects in K.13.